Seawater Intrusion Assessment based on Geological, Hydrogeological, Cl/Br vs Cl Graphical Analysis, Recharge Area, and Groundwater Usage in Makassar Coastal Area, South Sulawesi, Indonesia - Nugroho, Sunu Ardhi; Wilopo, Wahyu; Lathif, Iqbal Fuady Ahmad; Taufiq, Ahmad (Journal of Applied Geology, 2024)
Seawater intrusion is a major concern in coastal urban areas like Makassar, where groundwater is a crucial water source. This study assesses seawater intrusion using multiple approaches, including geological and hydrogeological analysis, Cl/Br vs. Cl graphical analysis, recharge area land use, groundwater usage, and previous seawater intrusion vulnerability mapping. From 20 groundwater samples, five were categorized as brackish and then analyzed using these six perspectives. Geologically, two shallow wells in Mariso and Manggala contain brackish water due to trapped marine sediments, supported hydrogeologically by local groundwater flow patterns indicating past shallow seawater traps, while wells in Tallo show no such indications. Cl/Br vs. Cl graphical analysis classifies the shallow well in Tallo as Seawater, one in Manggala as Brine Basin, and three others as landfill leachate, suggesting anthropogenic contamination. Most groundwater recharge areas are residential and built-up, limiting infiltration and contributing to seawater intrusion. Groundwater usage is highest in Tallo, moderately high in Mariso and Manggala, and moderate in Ujung Pandang. Vulnerability mapping places the Tallo well in a high-risk zone, the Mariso well in a low-risk zone, and the Manggala well in a non-vulnerable area. Across these perspectives, only one sample in the Tallo District is confirmed to experience seawater intrusion.